ارزیابی جامع میزان موفقیت بلوک پکتورال در جراحی‌های پستان - عزیزی فارسانی حمیدرضا; محسنی غلامرضا; Behnaz, fartanak; ansar, padideh; abniki, maliheh; تیموریان هومن (مجله انجمن آنستزیولوژی و مراقبت‌های ویژه ایران, 2025)
Abstract Background and Objective: The pectoral nerve block (PECS block) is recognized as one of the most effective techniques for postoperative analgesia in breast surgery. This systematic review and meta-analysis was conducted to evaluate the success rate of this technique based on published clinical studies. Materials and Methods: This study was conducted according to PRISMA guidelines. A systematic search was performed in Scopus, PubMed, Web of Science, and the Cochrane Library for studies published between 2011 and 2023. A random-effects model was used for the meta-analysis of 35 studies. Results: The pooled success rate of the pectoral nerve block was 92.4% (95% CI: 87.8–96.9%). The PECS II technique demonstrated a significantly higher success rate compared with PECS I (95% vs. 87%). Ultrasound guidance improved block success to 95%. Significant contributing factors included technique type, volume and type of local anesthetic, use of ultrasound, and operator experience. Conclusion: The pectoral nerve block is a highly effective technique for pain control after breast surgery. Its success is strongly influenced by technical and procedural variables. This article presents detailed success-rate statistics and a comprehensive comparative table of key studies and influencing factors. زمینه و هدف: بلوک پکتورال (PECS block) به‌عنوان یکی از مؤثرترین روش‌های کنترل درد پس از جراحی‌های پستان شناخته می‌شود. این مطالعه مروری سیستماتیک با هدف تحلیل دقیق میزان موفقیت این تکنیک بر اساس مطالعات بالینی منتشر شده انجام شد. مواد و روش‌ها: این مطالعه با بررسی سیستماتیک ۳۵ مطالعه بالینی منتشر شده بین سال‌های ۲۰۱۱ تا ۲۰۲۳ انجام گردید. یافته‌ها: میانگین میزان موفقیت بلوک پکتورال در کنترل درد پس از جراحی‌های پستان ۹۲٫۴٪ (دامنه ۸۵-۹۷٪) گزارش شد. عوامل متعددی بر این موفقیت تأثیر مستقیم داشتند، از جمله: نوع تکنیک PECS I (در مقابل PECS II)، حجم و نوع داروی بی‌حسی، استفاده از اولتراسوند و مهارت اپراتور. نتیجه‌گیری: بلوک پکتورال تکنیکی بسیار موفق در کنترل درد پس از جراحی پستان است. موفقیت آن تحت تأثیر عوامل فنی و اجرایی قابل‌توجهی قرار دارد. این مقاله علاوه بر ارائه آمار دقیق، جدول مقایسه‌ای جامعی از مطالعات کلیدی و عوامل مؤثر بر موفقیت بلوک را ارائه می‌دهد.